Evaluasi Kepercayaan Konsumen dalam Pembelian Stiker Label UMKM di Shopee dengan Metode Technology Acceptance Model (TAM) - Nisa, Khoirotun; Krisna, Dany Yudha (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
Lack of consumer trust can be caused by various factors, such as product quality that does not meet expectations, unsecured transactions, and lack of product information. Therefore, it is necessary to evaluate consumer trust in purchasing MSME label stickers on Shopee using the Technology Acceptance Model (TAM) method to understand the factors that influence consumer trust and purchase intent. This study aimed to analyze various factors that influence consumer trust in purchasing label sticker products from MSMEs on the Shopee platform using the Technology Acceptance Model (TAM) approach. The research approach used was qualitative descriptive, using a literature review method to examine various studies related to consumer trust, online purchasing behavior, and digital marketing. The results showed that consumer trust is influenced by four main factors: store reputation and buyer reviews, product information quality, visual branding through label design, and perceived ease and usefulness of using the Shopee platform. Store reputation and positive reviews build social trust, accurate product information strengthens cognitive trust, and attractive label design builds emotional trust. Perceived ease and usefulness of Shopee also increases consumer confidence and repurchase intention. The TAM model has proven relevant in explaining digital consumer behavior and provides practical implications for MSMEs in developing trust-based marketing strategies in e-commerce.